Inferiority feelings in the individual and the group - Oliver Brachfeld, F. (International library of psychology. Abnormal and clinical psychology ;, 2000)
This detailed book provides a compelling insight into how attitudes to states such as nervous anxiety and hysteria have changed over the past century. The evolution of approaches to and the deifnitions of the conditions are also included.